Evaluation of the quality of Amazonian butters as sustainable raw materials for applications in bioproducts - Jefferson Maia Feitosa; Thamires Souza de Alencar Silva; Ana Elizabete Xavier Fonseca; Wendel Clei Souza Rodrigues; Amanda Carolline Esquerdo da Silva; Cassia Valeria Pinheiro Correa; Fagner Sousa de Aguiar; Rosa Helena Veras Mourão; Edilene Gadelha de Oliveira; Kariane Mendes Nunes (São Paulo State University (UNESP), 2021)
A new consumer profile for pharmaceutical and cosmetic products has motivated research into natural raw materials in the development of "green" products such as herbal medicines and biocosmetics. However, various limitations have been encountered in the marketing of these products, for example the quality control of the natural raw materials used by the industrial market. This study aims to evaluate the sensory and physicochemical parameters of murumuru (Astrocaryum murumuru Mart.), bacuri (Platonia insignis Mart.), tucuma (Astrocaryum vulgare Mart.), and ucuuba (Virola sebifera Aubl.) butters for applications in pharmaceutical and cosmetic bioproducts. The acidity and saponification as well as the iodine and peroxide indexes were evaluated and fatty acid profiles for the samples obtained by GC-MS. The sensory properties of the butters showed the appearance of solid to soft cream, color (yellow, brown, buttercup, and ochre), and characteristic odor. The melting temperatures of all butters ranged between 31 ºC and 49 °C. The acidity, saponification, iodine and peroxide indexes for the butters were of 5.82 - 17.73 mg (NaOH or KOH) g−1, 181.10 - 573.55 mg KOH g−1, 2.78 - 44.96 gl2 100 g−1, and 1.39 - 9.30 meq kg−1, respectively. From analyses of the fatty acid profiles, the major components identified were lauric acid in murumuru (40%) and ucuuba butters (73%), myristic acid in tucuma butter (53%), and palmitic acid in bacuri butter (42%). In general, the results of the analyses differed from the specifications of the supplier reports and official compendia. These findings highlight the importance of quality control in natural raw materials to ensure their functionality in pharmaceutical and cosmetic bioproducts.